Comparative Analysis of Substrate-Free Cultured Oral Mucosal Epithelial Cell Sheets from Cells of Subjects with and without Stevens—Johnson Syndrome for Use in Ocular Surface Reconstruction - Kim, Yun Hee; Kim, Dong Hyun; Shin, Eun Jung; Lee, Hyun Ju; Wee, Won Ryang; Jeon, Saewha; Kim, Mee Kum (PloS one, 2016)
To compare the regenerative potential of cultured oral mucosal epithelial cells sheets (COMECs) from Stevens-Johnson syndrome (SJS) subjects with those from non-SJS subjects. Human oral mucosal epithelial cells from SJS and non-SJS subjects were cultured, and colony-forming efficiency (CFE), proliferative and migration potential, expression of cytokines/growth factors and stem cells were compared. COMECs from SJS and non-SJS subjects were transplanted into 12 limbal stem cell-deficient rabbits, and their regenerative potential was analyzed at 1 week after transplantation. CFE (p>0.05, student's t test), cell proliferation potential (p>0.05, two-way ANOVA) and expression of the cytokeratins (K3, K4, K13, K19) in the oral mucosal epithelial cells from SJS subjects were similar to those of the cells from non-SJS subjects. The initial migratory potential of SJS cells was delayed compared to that of non-SJS cells (p <0.05, RM two-way ANOVA). The SJS cells expressed lower levels of EGF and higher levels of VEGF compared to that of non-SJS cells (p<0.05, one-way ANOVA). In vivo transplanted SJS-COMECs showed similar expression of K3, K4, and K13, proliferation markers (Ki-67; p>0.05, Mann-Whitney U test), and stem cell markers (p63; p>0.05, Mann-Whitney U test) compared to non-SJS COMECs. The initial epithelial defects in vivo were larger in the eyes treated with SJS-COMECs on day 3 (p<0.01, RM two-way ANOVA), but no differences were observed by day 7 between SJS- and non-SJS-COMECs. These results suggest that, aside from differences in migratory potential, oral mucosal epithelial cells from SJS and non-SJS subjects are comparable in their regeneration potential in treating limbal stem cell deficiency.